Pengurangan Resiko Bencana Berbasis Komunitas di Desa Kemasantani Kecamatan Gondang Kabupaten Mojokerto - Rarasaning Satianingsih; Sunu Catur Budiyono; Marianus Subandowo; Nurmida Catherine Sitompul (Kanigara, 2022)
Disasters are an inseparable part of an area, both natural disasters, non-natural disasters, and social disasters. Disasters have become a phenomenon that must be continually examined given the enormous impact that the region has had when they are not prepared to deal with it. In various countries, especially Indonesia, there are various kinds of disasters, including floods, tornadoes, and avalanche land. Disaster problems such as this are priority problems, due to the large frequency of disasters and the extent of their priority handling. Community-Based Disaster Risk Reduction, given that the magnitude of disaster victims is the people living in disaster disasters who first face disasters are the people themselves, efforts should be made to improve the basic and capacity of the community in anticipating the possibility of disasters occurring at their area, so that disaster risk can be reduced and prevented.